"Economic Policies for Development: Beyond the Millenium Goals". Ed. Nova Science Editors, Nueva York (EE.UU.) ISBN 9781536171389, 2020, 304 páginas. Díaz Roldán, C.; Pérez Ortiz, L. y Da Silva Bichara, J. (eds.) - Merino de Lucas, Fernando (Revista de Economía Mundial, 2021)
Reseña del libro Díaz Roldán, C., Pérez Ortiz, L. y da Silva Bichara, J. eds. (2020): “Economics Policies for Development: Beyond the millenium goals”. Ed. Nova Science Editors, Nueva York (EE.UU.) ISBN 9781536171389